2008
DOI: 10.1007/s11250-008-9193-7
|View full text |Cite
|
Sign up to set email alerts
|

Performance of growing indigenous goats fed diets based on urban market crop wastes

Abstract: The effect of feeding diets including market crop wastes (sweet potato vines (Ipomoea batatas) and scarlet eggplant (Solanum aethiopicum)) on growth and digestibility was studied using 32 indigenous intact growing male goats. Adding elephant grass (Pennisetum purpureum), maize bran and Leucaena leucocephala leaves, four isocaloric and isonitrogenous diets (Sweet potato vines, Solanum, Mixed and Control) were formulated. After the growth trial, 12 goats were randomly selected for a digestibility trial with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0
4

Year Published

2009
2009
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 13 publications
4
5
0
4
Order By: Relevance
“…This is in agreement with a recent study by Katongole et al (2009), who indicated that the increase in faecal N excretion with a decline in urinary N excretion is associated with tannin-protein complexes when goats were fed Leucaena leaves. When expressing N retention as a percentage of N intake, the value ranged from 58 to 69% in the present study, which is high since N retention normally is around 19% of the intake (Hill et al 2007).…”
Section: Effects Of Supplementationsupporting
confidence: 93%
“…This is in agreement with a recent study by Katongole et al (2009), who indicated that the increase in faecal N excretion with a decline in urinary N excretion is associated with tannin-protein complexes when goats were fed Leucaena leaves. When expressing N retention as a percentage of N intake, the value ranged from 58 to 69% in the present study, which is high since N retention normally is around 19% of the intake (Hill et al 2007).…”
Section: Effects Of Supplementationsupporting
confidence: 93%
“…The low DM intake of the SEPD observed is attributed to the low acceptability of SEP. Similar results of low acceptability of scarlet eggplant wastes by goats, and hence loss of BW were reported by Katongole et al (2008Katongole et al ( , 2009). However, the low acceptability of SEP can not be easily explained.…”
Section: Intake Growth Rate and Carcass Yieldsupporting
confidence: 85%
“…The chemical composition of the market crop wastes in this study was in the range reported previously by Katongole et al (2008Katongole et al ( , 2009. The CP content of elephant grass observed in this study was lower than that reported by Kariuki et al (1998) and Kabi et al (2005).…”
Section: Chemical Composition Of Feedssupporting
confidence: 72%
See 2 more Smart Citations